Vaginal and Penile Microbiome Associations With Herpes Simplex Virus Type 2 in Women and Their Male Sex Partners. (21st August 2020) - Mehta, Supriya D; Nandi, Debarghya; Agingu, Walter; Green, Stefan J; Bhaumik, Dulal K; Bailey, Robert C; Otieno, Fredrick
Abstract: Background: We determined how the vaginal and penile microbiomes contribute to herpes simplex virus type 2 (HSV-2) serostatus within sexual partnerships. Methods: Microbiomes were characterized in cervicovaginal lavage and penile meatal swab specimens through high-throughput 16s ribosomal RNA gene amplicon sequencing. HSV-2 antibody was detected in serum specimens. We modeled vaginal and penile taxa and covariates contributing to HSV-2 status in women and men using bivariate probit analysis. Results: Among 231 couples, HSV-2 was detected in both partners in 78 couples (33.8%), in the woman only in 52 (22.5%), in the man only in 27 (11.7%), and in neither in 74 (32.0%). Among the women (median age, 22 years) 10.9% had human immunodeficiency virus (HIV), and 21.4% had Bacterial vaginosis. Among men (median age, 26 years), 11.8% had HIV, and 55.0% circumcised. In an analysis with adjustment for sociodemographics and Bacterial vaginosis, enrichment of vaginal Gardnerella vaginalis and Lactobacillus iners was associated with increased likelihood of HSV-2 in both partners. Penile taxa (including Ureaplasma and Aerococcus ) were associated with HSV-2 in women. Conclusions: We demonstrate that penile taxa are associated with HSV-2 in female partners, and vaginal taxa are associated with HSV-2 in male partners. Our findings suggest that couples-level joint consideration of genital microbiome and sexually transmitted infection or related outcomes could lead to new avenues for prevention. Abstract : Penile taxa are associated with herpes simplex virus type 2 (HSV-2) in female partners, and vaginal taxa with HSV-2 in male partners. Couples-level consideration of the genital microbiome could open new avenues for preventing sexually transmitted infection and related outcomes.